Peningkatan Kualitas Pembelajaran Siswa Tunagrahita dalam Membaca dan Menulis melalui Pendekatan Kooperatif Tipe STAD di Sekolah Luar Biasa - Murtadlo Murtadlo (Universitas Negeri Yogyakarta, 2006)
The study attempts to improve the achievement of the student with early reading and writing difficulties. The research is designed experimentally. To collect the data, instrumens of test, documentation adn observation are used. The data were analised using non parametric statistic :